Electrical effects of stem cell transplantation for ischaemic cardiomyopathy: friend or foe?. (19th January 2016) - Mount, Seth; Davis, Darryl R.
Abstract : Potential effects of stem cell transplantation on electrical remodeling after myocardial infarction. Abstract: Despite advances in other realms of cardiac care, the mortality attributable to ischaemic cardiomyopathy has only marginally decreased over the last 10 years. These findings highlight the growing realization that current pharmacological and device therapies rarely reverse disease progression and rationalize a focus on novel means to reverse, repair and re‐vascularize damaged hearts. As such, multiple candidate cell types have been used to regenerate damaged hearts either directly (through differentiation to form new tissue) or indirectly (via paracrine effects). Emerging literature suggests that robust engraftment of electrophysiolgically heterogeneous tissue from transplanted cells comes at the cost of a high incidence of ventricular arrhythmias. Similar electrophysiological studies of haematological stem cells raised early concerns that transplant of depolarized, inexcitable cells that also induce paracrine‐mediated electrophysiological remodelling may be pro‐arrhythmic. However, meta‐analyses suggest that patients receiving haematological stem cells paradoxically may experience a decrease in ventricular arrhythmias, an observation potentially related to the extremely poor long‐term survival of injected cells. Finally, early clinical and preclinical data from technologies capable of differentiating to a mature cardiomyocyte phenotype (such as cardiac‐derived stem cells) suggests that these cells are not pro‐arrhythmic although they too lack robust long‐term engraftment. These results highlight the growing understanding that as next generation cell therapies are developed, emphasis should also be placed on understanding possible anti‐arrhythmic contributions of transplanted cells while vigilance is needed to predict and treat the inadvertent effects of regenerative cell therapies on the electrophysiological stability of the ischaemic cardiomyopathic heart.